Evaluation of a recombinant multiepitope antigen for diagnosis of hepatitis C virus: A lower cost alternative for antigen production. Issue 6 (17th February 2018) - Thomasini, Ronaldo Luis; Souza, Hortencia Gisele Amaro; Bruna‐Romero, Oscar; Totola, Antonio Helvecio; Gonçales, Neiva Sellan Lopes; Lima, Cristiano Xavier; Teixeira, Mauro Martins
Abstract : Background: The most of the hepatitis C‐infected patients remain undiagnosed until they develop severe liver damage or submitted for serological screening. Objective: To evaluate a recombinant multiepitope protein for detection of IgG anti‐hepatitis C virus. Method: A synthetic gene was cloned, expressed in Escherichia coli, and the recombinant protein was purified. Human serum panel consisted of 88 positives (20 HCV genotyped) and 376 negatives for hepatitis C, 6 positives for human acquired immunodeficiency virus, 6 syphilis positives, 6 hepatitis B positives were tested by IgG antihepatitis C virus using the protein by enzyme‐linked immunosorbent assay. In addition, 20 positive (all genotyped samples) and 20 negative samples were also tested by immunoblot and dot blot assays. Results: Positive hepatitis C sera were strongly reactive against the protein by immunoblot assay. In the dot blot assay, positive sera were reactive until 1:1000 dilution and there were no false positive results in the hepatitis C negative sera. In the enzyme‐linked immunosorbent assay, positive and negative sera had significant discrimination. No cross‐reaction was observed in samples positive for syphilis; human acquired immunodeficiency virus and hepatitis B. All 20 genotyped samples were positive by the three methods. Conclusion: The multiepitope protein used here has a lower cost compared to production of each antigen separately and could be an alternative for the serological diagnosis of hepatitis C.